The evaluation of research by scientometric indicators - Vinkler, Peter (Chandos information professional series., 2010)
Reviews the principles, methods and indicators of scientometric evaluation of information processes in science and assessment of the publication activity of individuals, teams, institutes and countries. The book provides scientists, science officers, librarians and students with basic and advanced knowledge on evaluative scientometrics.